Geriatric Nutrition Risk Index: Prognostic factor related to inflammation in elderly patients with cancer cachexia. Issue 6 (29th September 2021) - Ruan, Guo‐Tian; Zhang, Qi; Zhang, Xi; Tang, Meng; Song, Meng‐Meng; Zhang, Xiao‐Wei; Li, Xiang‐Rui; Zhang, Kang‐Ping; Ge, Yi‐Zhong; Yang, Ming; Li, Qin‐Qin; Chen, Yong‐Bing; et al.
Abstract: Background: Systemic inflammation and cachexia are associated with adverse clinical outcomes in elderly patients with cancer. The Geriatric Nutritional Risk Index (GNRI) is a simple and useful tool to assess these conditions, but its predictive ability for elderly patients with cancer cachexia (EPCC) is unknown. Methods: This multicentre cohort study included 746 EPCC with an average age of 72.00 ± 5.24 years, of whom 489 (65.5%) were male. The patients were divided into two groups (high GNRI group ≥91.959 vs. low GNRI group <91.959) according to the optimal cut‐off value of the ROC curve. The calibration curves were performed to analyse the prognostic, predictive ability of GNRI. Comprehensive survival analyses were utilized to explore the relationship between GNRI and the overall survival (OS) of EPCC. Interaction analysis was used to investigate the comprehensive effects of low GNRI and subgroup parameters on the OS of EPCC. Results: In this study, a total of 2560 patients were diagnosed with cancer cachexia, including 746 cases of EPCC. During the 3.6 year median follow‐up, we observed 403 deaths. The overall mortality rate for EPCC at 12 months was 34.3% (95% CI: 62.3% to 69.2%), and resulting in rate of 278 events per 1000 patient‐years. The GNRI score of EPCC was significantly lower than those of young patients with cancer cachexia ( P < 0.001). The 1, 3, and 5 year calibration curves showed that the GNRI score had good survival prediction in the OS of EPCC. The GNRI could predict the OS of EPCC, whether as a continuous variable or a categorical variable. Particularly, we also found that low GNRI score (<91.959) of EPCC had a worse prognosis than those with a high GNRI score (≥91.959, P = 0.001, HR = 1.728, 95% CI: 1.244–2.401). Consistent results were observed in the tumour subgroups of gastric cancer and colorectal cancer. Notably, similar results were observed in the sensitivity analysis. In the subgroup analysis, the low GNRI has a combined effect with age (<70 years) on poor OS of EPCC. The results of the prognostic risk model found that the lower the GNRI score, the greater the prognostic risk score, and the greater the risk of death in EPCC. Conclusions: For the first time, this study found that the GNRI score can serve as an independent prognostic factor for the OS of EPCC.